Effect of Rumen Protected Niacin Supplementation on Blood Biochemical Analytes during Transition Period in Surti Goats - D Manat, Tanvi; S Chaudhary, Sandhya; Kumar Singh, Virendra; B Joshi, Axay; M Pandya, Gaurav (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
The present study was conducted to evaluate the effect of rumen protected niacin (RPN) supplementation on blood biochemical analytes during transition phase in Surti goats. Eighteen pregnant Surti goats were divided into two groups as control (CON, n=9) and treatment (RPN, n=9). RPN group was supplemented with RPN @ 1.5 g/animal/day from -2 to +8 weeks of kidding. Biweekly blood samples were collected from -2 to +10 weeks of kidding for analyzing biochemical parameters. Significant (p≤0.05) beneficial effects of RPN supplementation in lowering of pyruvate and lactate was observed at 0, +4 and +6 week; hepatic enzymes (GGT, ALT, AST, GDH) at 0, +2, +4 and +6 week; Urea at 0 and +6 week, whereas creatinine at 0, +2 and +6 weeks. RPN supplementation was also advantageous in significantly (p≤0.05) elevating triglycerides at 0 and +6 week, cholesterol at 0, 4 and +6 week, whereas LDL-C and HDL-C at 0 week. It was thus concluded that rumen protected niacin supplementation @ 1.5 g/day during transition period in Surti goats mitigates metabolic dysregulation.